2019
DOI: 10.1128/aem.02420-18
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Enteroviruses from Cattle and Goat Feces and Environment in Thailand

Abstract: The identification and characterization of viruses of the genus Enterovirus in healthy and infected livestock, including cattle and goats, have been increasing. Enterovirus E (EV-E) and Enterovirus F (EV-F) are commonly found in cattle, whereas Enterovirus G (EV-G) is found in goats. In this study, molecular and phylogenetic analyses were performed to determine the prevalence of EVs in cattle and goat feces from Kanchanaburi Province, Thailand. The presence of EVs in water samples and the feces of other animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In contrast, no CPE was observed with fecal extracts from animal #5915, although the stx2 gene was amplified from the same sample ( Table 2 , Supplementary Figure 2 ), indicating a possibly nonfunctional gene. Additionally, non-Stx factors in the fecal extracts, such as viruses, may have caused CPE observed with 3/58 fecal extracts (animals #6044, #6069, and #6148) that were not neutralized with the anti-Stx antisera (Supplementary Figure 3 ) [ 77 , 78 ]. These variations indicate that Vero cell cytotoxicity assays require verification through neutralization steps and correlation with culture/PCR results.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, no CPE was observed with fecal extracts from animal #5915, although the stx2 gene was amplified from the same sample ( Table 2 , Supplementary Figure 2 ), indicating a possibly nonfunctional gene. Additionally, non-Stx factors in the fecal extracts, such as viruses, may have caused CPE observed with 3/58 fecal extracts (animals #6044, #6069, and #6148) that were not neutralized with the anti-Stx antisera (Supplementary Figure 3 ) [ 77 , 78 ]. These variations indicate that Vero cell cytotoxicity assays require verification through neutralization steps and correlation with culture/PCR results.…”
Section: Resultsmentioning
confidence: 99%
“…Aichivirus C was detected by a RT‐PCR assay that targeted the 3D gene according to our previous report, with a limit at 2.87 × 10 3 copies per microliter (Abi et al., 2020). Peste des Petits Ruminants, rotavirus A, bovine coronavirus, bovine viral diarrhoea virus, caprine enterovirus, enterotoxigenic Escherichia coli K99 and Salmonella were detected by RT‐PCR or PCR assays, as described previously (Amine et al., 2020; Brichta‐Harhay et al., 2013; Gong et al., 2014; Income et al., 2019; Polci et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Out of the 12 enterovirus species, EV-E and EV-F viruses infect cattle [ 2 , 3 , 4 , 5 , 6 , 7 ], while EV-G viruses generally infect pigs [ 8 , 9 , 10 , 11 ]. Recently, several enterovirus strains isolated from goats or sheep were also classified as EV-G [ 12 , 13 , 14 , 15 ]. Chang et al reported the caprine enterovirus strain SD-S67 isolated in cell culture from samples collected from goats as being EV-F, suggesting that goats are also natural hosts for EV-F [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caprine/ovine enterovirus (CEV/OEV) infection has been increasingly reported in recent years [ 12 , 13 , 14 , 15 ]. However, the genetic variation and evolution of caprine enterovirus has scarcely been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation